2020
DOI: 10.1007/s10943-020-01064-x
|View full text |Cite
|
Sign up to set email alerts
|

A Look at the First Quarantined Community in the USA: Response of Religious Communal Organizations and Implications for Public Health During the COVID-19 Pandemic

Abstract: The current study examined anxiety and distress among members of the first community to be quarantined in the USA due to the COVID-19 pandemic. In addition to being historically significant, the current sample was unusual in that those quarantined were all members of a Modern Orthodox Jewish community and were connected via religious institutions at which exposure may have occurred. We sought to explore the community and religious factors unique to this sample, as they relate to the psychological and public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 24 publications
3
51
0
1
Order By: Relevance
“…One of the few studies that investigated the influence of R/S on health outcomes during the COVID-19 pandemic ( Weinberger-Litman et al, 2020 ) included 303 members of North American religious communities and found no association between religious commitment with distress or anxiety. According to the authors, the lack of association is because this population is very religious and composed of members of specific religious traditions which may lead to a low variability of responses and minimized the statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies that investigated the influence of R/S on health outcomes during the COVID-19 pandemic ( Weinberger-Litman et al, 2020 ) included 303 members of North American religious communities and found no association between religious commitment with distress or anxiety. According to the authors, the lack of association is because this population is very religious and composed of members of specific religious traditions which may lead to a low variability of responses and minimized the statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…And we observe this importance in our results, as both conservative and liberal communication resources were found to exert strong influence on the network and facilitate communication activity across the network. Additionally, during a public health emergency, local organizations may be important and trusted sources of information and resources ( Weinberger-Litman et al, 2020 ), which explains their importance in the COVID-19 communication ecology observed here.…”
Section: Discussionmentioning
confidence: 83%
“…Twenty-six studies reported on the mitigating role of religion during the early stage of COVID-19 (Ahmed & Memish, 2020 ; Al-Rousan & Al-Najjar, 2020 ; Ali & Alharbi, 2020 ; Atique & Itumalla, 2020 ; Crubézy & Telmon, 2020 ; Ebrahim & Memish, 2020a , 2020b ; Escher, 2020 ; Frei-Landau, 2020 ; Gautret et al, 2020 ; Ha, 2020 ; Hong & Handal, 2020 ; Iqbal et al, 2020 ; Kim et al, 2020 ; McCloskey, et al, 2020a , 2020b ; Memish et al, 2020 ; Muurlink & Taylor-Robinson, 2020 ; Quadri, 2020 ; Tarimo & Wu, 2020 ; Waitzberg et al, 2020 ; Weinberger-Litman et al, 2020 ; Wildman et al, 2020 ; Wong et al, 2020 ; Yezli & Khan, 2020a , 2020b ) (Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…During the early stage of COVID-19, various religious institutions have collaborated with science sector and government authorities to innovate new measures of continuing religious commitments and rituals through social networks, TV channels, or live streaming (Capponi, 2020 ; Frei-Landau, 2020 ). These new innovative measures following public health information have been effectively implemented by religious leaders as some religious believers tend to have more faith in religious leaders than science or public health guidelines (Kim et al, 2020 ; Quadri, 2020 ; Weinberger-Litman et al, 2020 ). This clearly demonstrates how powerful religious leaders can be in delivering public health messages and highlights the importance of collaborating with religious sectors when facing public health crises.…”
Section: Discussionmentioning
confidence: 99%